Seronegative brucellosis of the spine: A case of psoas abscess secondary to brucellar spondylitis - Bozbaş, Gülnur Taşcı (Eur J Rheumatol, 2016)
Brucellosis is an infectious disease that affects many organ systems. Osteoarticular involvement, especially spondylitis, is the most common complication of brucellosis, but psoas abscess is very rare. Serological tests at diagnosis of the disease are very valuable and most widely used. Herein, we report a case of psoas abscess secondary to brucellar spondylitis. In this case, interestingly, the serological test results were negative, and the diagnosis could be made by abscess culture. In patients, particularly those who live in areas endemic for brucellosis, as in our case, it should be kept in mind that a negative serological test result should not exclude the diagnosis of brucellosis.